Experimental analysis of the efficiency of gamma-ray spectrum smoothing with LS-SVM when using a compact scintillation detector. - Mischenko, Egor; Nikitin, Aleksander; Solonenko, Evgenia (Journal of the Belarusian State University. Ecology, 2024)
Improving methods for processing gamma-ray spectrograms is a highly promising direction for further advancements in determining the content of radionuclides in environmental objects. A significant challenge lies in smoothing spectra during in situ measurements due to time constraints and low signal-to-noise ratio. This study evaluates the effectiveness of using Least Squares Support Vector Machine (LS-SVM) regression for smoothing spectra obtained with a NaI(Tl) scintillation detector, comparing it with moving average and exponential smoothing methods. The evaluation of spectrum alignment effectiveness was conducted for the entire energy measurement range. Semi-synthetic gamma-ray spectra with measurement times 60, 300, 900, 1800, 3600, 7200, and 72000 seconds, generated by channel summing of randomly selected real spectra converted into count rates, were employed for analysis. Real spectra were acquired using an experimental setup consisting of an ATOMTEX detection unit, a radionuclide source, a computer with specialized software, and auxiliary devices. The analysis demonstrated that the LS-SVM method is most effective for smoothing spectrograms obtained at measurement times ranging from 1·103 to 7·103 seconds. Separate optimization of smoothing model hyperparameters is required for three partially overlapping energy subranges. For more longer measurements, applying tested spectrogram smoothing methods does not reduce the signal-to-noise ratio. For short intervals (up to 100 seconds), the moving average method exhibits the highest efficiency, allowing for a 2–2.5 dB improvement in the signal-to-noise ratio. In the measurement time range of 102–103 seconds, the most effective suppression of statistical noise is achieved with exponential smoothing with α = 0.75.
Keywords: gamma-spectrometry; spectrum unfolding; ignal-to-noise ratio; support vector regression